Optimization and Enhancement of Catechin Production by Endophytic Fungi Isolated from Camellia sinensis - Singh, Shruti (Thapar Institute of Engineering and Technology, 2025)
Catechins are powerful polyphenolic chemicals exhibiting notable antioxidant, anti-inflammatory, and anticancer characteristics, typically derived from tea plants (Camellia sinensis). The investigation of endophytic fungi as alternate sources for catechin synthesis offers a viable biotechnological strategy to address the limitations of plant-based extraction methods. This study examined the optimization and augmentation of catechin production by endophytic fungi derived from C. sinensis to establish an effective microbial production system for these key medicinal chemicals. The study concentrated on a particular fungal strain coded as PP5B, extracted from tea plant tissues and subjected to thorough morphological and molecular analysis. The fungal isolate had unique morphological characteristics, including a dense, cottony to woolly mycelial texture, homogeneous white pigmentation, and septate hyphae with prominent cross-walls. The CTAB method was employed for genomic DNA extraction, followed by amplification of the internal transcribed spacer (ITS) by PCR region for molecular identification, with sequencing results awaited for conclusive taxonomic categorization. A systematic optimization strategy was utilized, incorporating both the one-variable-at-a-time technique and RSM, to identify optimal culture conditions for maximal catechin synthesis. The study assessed many aspects, including radial growth characteristics across distinct media types, growth variability throughout diverse incubation durations, pH optimization, and the interacting effects of agitation speed, incubation duration, and pH. The assessment indicated that the isolate attained a maximum radial growth of 8 cm on day 5, with optimal growth occurring at pH 4.5. The RSM study utilized a Central Composite Design with 17 experimental runs to optimize three essential parameters: agitation speed (0-120 rpm), incubation duration (5-15 days), and pH (4.5-7.5). UV-Visible Spectrophotometry and High-Performance Liquid Chromatography (HPLC) were employed for the accurate quantification of catechin production. The mathematical model created via RSM exhibited statistical significance with an F-value of 30.90 (p < 0.0001) and a coefficient of determination (R²) of 0.8114, signifying strong model fit. The model equation indicated that agitation speed, incubation duration, and pH were significant variables, in addition to specific interaction terms (AC and BC) and the quadratic term C². This study effectively illustrates the possibility of endophytic fungi from C. sinensis as a viable VIII | P a g e and sustainable source for catechin synthesis. The improved fermentation parameters establish a basis for scaling up the production process, presenting benefits such as regulated production conditions, less reliance on seasonal fluctuations, and opportunities for genetic improvement. This study greatly advances microbial biotechnology and natural product synthesis, offering useful insights into optimizing bioactive compound biosynthesis by endophytic fungi. Future study directions may encompass scale-up investigations, genetic modification for improved production, and thorough analysis of the catechin profile generated by the fungal system.
Keywords: Endophytic Fungi; Catechin; Camellia sinensis; Antioxidant; Polyphenolic Chemicals